Angel - Miles, Ellen (Miles, Ellen. Puppy place., 2017)
Going to considerable lengths to rescue a dog stranded in the woods, Lizzie helps her parents foster the adorable Havanese, whose playful nature and difficult experiences make finding her a forever home particularly challenging.